Migration and School: Documentary Analysis on the Incorporation of Immigrants into the Chilean Educational System [Migración y Escuela: Análisis Documental en Torno a la Incorporación de Inmigrantes Al Sistema Educativo Chileno] - Aguilera-Valdivia, M; Hernandez-Yañez, M (Pontificia Universidad Catolica de Valparaiso, 2017)
One of the weaknesses of programs aimed at receiving immigrant students into Chilean schools is the absence of educational guidelines that may orient its management and help organizing their incorporation. This study presents the results of a documentary analysis on the schooling of immigrant students. By means of an analysis of semantic content of 82 documentary sources, explanatory categories were constructed allowing to identify certain patterns, tensions and conducting threads. The results analyze the main areas of action (access and enrollment), the nature of the documents (informative and instructive) as well as the predominant approaches to cultural diversity (rights approach and multiculturalism). Findings show the current state as well as the existing challenges for the development of reception strategies that promote greater equity and educational justice. We discuss the need to expand work to other areas, and to promote new approaches to cultural diversity through documents that can advise and guide the work carried out by the educational communities.
Keywords: Documentary analysis; Migration; Multiculturalism; Reception programs; School